Variability in Clinical Observations and Treatment Decisions Among Therapists for Knee Injury - Ibrahim Milad Jibril Mohammed; AL Tihaml Abd elsalam Abdullah AL Talep (Libyan Journal of Medical and Applied Sciences, 2025)
Variability in how clinicians observe and treat knee injuries can impact patient outcomes and guideline adherence. We review literature on inter-clinician reliability and practice patterns. Studies report moderate-to-high agreement on specific physical tests (e.g., Lachman κ≈0.42-0.81), but notable differences in how therapists classify conditions and select treatments. Surveys indicate nearly all therapists use exercise for knee osteoarthritis, yet only 34% plan post-discharge follow-up. Older therapists favor passive modalities (e.g., 19% use ultrasound). Chart reviews of postoperative rehab show large variations in visit counts and exercise types by setting. Qualitative studies reveal that many therapists tailor care based on symptoms and often use “non-core” modalities (like manual therapy) despite guideline focus on education/exercise. Key factors include training background, clinical setting, and patient factors. These findings suggest a need for stronger consensus and training to reduce unwarranted variability, while preserving individualized care.